Induction of mast cell accumulation by chymase via an enzymatic activity‐ and intercellular adhesion molecule‐1‐dependent mechanism. (18th January 2018) - Zhang, Huiyun; Wang, Junling; Wang, Ling; Zhan, Mengmeng; Li, Shigang; Fang, Zeman; Xu, Ciyan; Zheng, Yanshan; He, Shaoheng
Abstract : Background and Purpose: Chymase is a unique, abundant secretory product of mast cells and a potent chemoattractant for eosinophils, monocytes and neutrophils, but little is known of its influence on mast cell accumulation. Experimental Approach: A mouse peritoneal inflammation model, cell migration assay and flowcytometry analysis, were used to investigate the role of chymase in recruiting mast cells. Key Results: Chymase increased, by up to 5.4‐fold, mast cell numbers in mouse peritoneum. Inhibitors of chymase, heat‐inactivation of the enzyme, sodium cromoglycate and terfenadine, and pretreatment of mice with anti‐intercellular adhesion molecule 1, anti‐L‐selectin, anti‐CD11a and anti‐CD18 antibodies dramatically diminished the chymase‐induced increase in mast cell accumulation. These findings indicate that this effect of chymase is dependent on its enzymatic activity and activation of adhesion molecules. In addition, chymase provoked a significant increase in 5‐HT and eotaxin release (up to 1.8‐ and 2.2‐fold, respectively) in mouse peritoneum. Since 5‐HT, eotaxin and RANTES can induce marked mast cell accumulation, these indirect mechanisms may also contribute to chymase‐induced mast cell accumulation. Moreover, chymase increased the trans‐endothelium migration of mast cells in vitro indicating it also acts as a chemoattractant. Conclusion and Implications: The finding that mast cells accumulate in response to chymase implies further that chymase is a major pro‐inflammatory mediator of mast cells. This effect of chymase, a major product of mast cell granules, suggests a novel self‐amplification mechanism for mast cell accumulation in allergic inflammation. Mast cell stabilizers and inhibitors of chymase may have potential as a treatment of allergic disorders.